Dampak Set Peluang Investasi Terhadap Nilai Perusahaan Publik di Bursa Efek Jakarta - Sri Hasnawati (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2005)
The objective of this research is to get an understanding on the effect of investment deci¬sions on value of a company using Structural Equation Model (SEM). It is expected that this model will give more comprehensive analysis on the effect of the investment decisions on value of the fir. This analysis was based on target population of 259 public companies at Jakarta Stock Exchange, with following finding.The investment decision effect on the value of the companies, respectively 12,25%. The theoretical finding on this research can be developed to make an investment decision at stock ex¬change. In other words, the investment decision made by companies will have some means of effect on company’s value compare with other factors.Keywords: structural equation mode, invest¬ment opportu¬nity set, return saham, market value